METHOD OF DETERMINING THE COP COEFFICIENT FOR A COOLING SYSTEM - Rzasa, Mariusz; Pochwała, Sławomir; Szymaniec, Sławomir (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
The basic metrological problem analyzed in this article is the experimental determination of the COP coefficient for a refrigerating system working in a stationary cooling chamber. This issue is because manufacturers of chillers provide the value of this coefficient in device technical data. In practice, after installing the refrigeration unit, the COP is often lower. The paper presents a method of balancing cooling energy for a complete refrigeration system.